EFL Pre-Service Teachers' Beliefs in Microteaching Practicum - Herdiawan, Rama Dwika (Allure Journal, 2023)
Pre-service teachers' expectation in order to successfully carry out the instructional process in the classroom is for them to create the most of their educational experiences by conveying their knowledge to the students. In this study, a case study was implemented, and it consisted of eleven future English teachers participating in a microteaching practicum that was led by two senior lecturers. The whole parties were aware of the purpose of the investigation that was being conducted. Based on the findings, pre-service teachers are almost unanimously of the opinion that one of the most significant aspects of the process of teaching and learning English is the contact that occurs in English between the teacher and the students. When teachers communicate in English with their students, those students are more likely to make an effort to communicate in English on their own. Therefore, English teachers should consistently encourage their pupils to use English throughout the entirety of the teaching and learning process with their classes.